Effects of short‐to‐long term enzyme replacement therapy (ERT) on skeletal muscle tissue in late onset Pompe disease (LOPD). (4th July 2017) - Ripolone, M.; Violano, R.; Ronchi, D.; Mondello, S.; Nascimbeni, A.; Colombo, I.; Fagiolari, G.; Bordoni, A.; Fortunato, F.; Lucchini, V.; Saredi, S.; Filosto, M.; et al.
Abstract : Aims: Pompe disease is an autosomal recessive lysosomal storage disorder resulting from deficiency of acid α‐glucosidase (GAA) enzyme. Histopathological hallmarks in skeletal muscle tissue are fibre vacuolization and autophagy. Since 2006, enzyme replacement therapy (ERT) is the only approved treatment with human recombinant GAA alglucosidase alfa. We designed a study to examine ERT‐related skeletal muscle changes in 18 modestly to moderately affected late onset Pompe disease (LOPD) patients along with the relationship between morphological/biochemical changes and clinical outcomes. Treatment duration was short‐to‐long term. Methods: We examined muscle biopsies from 18 LOPD patients at both histopathological and biochemical level. All patients underwent two muscle biopsies, before and after ERT administration respectively. The study is partially retrospective because the first biopsies were taken before the study was designed, whereas the second biopsy was always performed after at least 6 months of ERT administration. Results: After ERT, 15 out of 18 patients showed improved 6‐min walking test (6MWT; P = 0.0007) and most of them achieved respiratory stabilization. Pretreatment muscle biopsies disclosed marked histopathological variability, ranging from an almost normal pattern to a severe vacuolar myopathy. After treatment, we detected morphological improvement in 15 patients and worsening in three patients. Post‐ERT GAA enzymatic activity was mildly increased compared with pretreatment levels in all patients. Protein levels of the mature enzyme increased in 14 of the 18 patients (mean increase = +35%; P < 0.05). Additional studies demonstrated an improved autophagic flux after ERT in some patients. Conclusions: ERT positively modified skeletal muscle pathology as well as motor and respiratory outcomes in the majority of LOPD patients.